Materialism, Body Surveillance, Body Shame, and Body Dissatisfaction: Testing a Mediational Model - Sun, Qingqing (Frontiers in Psychology, 2018)
The present study aimed to examine the mechanisms underlying the links between materialism and body dissatisfaction. A sample of 583 Chinese undergraduate women completed a questionnaire measuring materialism, body surveillance, body shame, and body dissatisfaction. Correlational analysis showed that materialism, body surveillance, and body shame were significantly positively correlated with body dissatisfaction. The results of path analyses revealed that higher materialism predicted more body dissatisfaction, albeit indirectly, via higher body surveillance and body shame.